A biblical text and its afterlives : the survival of Jonah in western culture - Sherwood, Yvonne (Cambridge, U.K. ; New York : Cambridge University Press, 2000)
This book charts the mutations of a particularly buoyant sliver of Bible text - the book of Jonah - as it latches onto Christian and Jewish motifs and anxieties, passes through highbrow and lowbrow culture, and finally becomes something of a scavenger among the ruins, as, in its most resourceful move to date, it begins to live off the demise of faith. Written at a point between Cultural Studies, Jewish Studies, Literature and Art, this book is concerned with those versions of the biblical that escape proper disciplinary boundaries: it shifts the focus from 'Mainstream' to 'Backwater' interpretation. It is less a navigation of interpretative history and more an interrogation of larger political/cultural issues: anti-Judaism in Biblical Studies, the secularisation of the Bible, and the projection of the Bible as credulous ingenu, naive Other to our savvy post-Enlightenment selves.
List of illustrations -- Acknowledgements -- -- Introduction. Marvellous excess and monstrous mutations : on dishing up and spinning (out) biblical words -- -- 1. The mainstream -- 1. Jonah and the Fathers : Jonah and Jesus as typological twins -- 2. Jonah the Jew : the evolution of a biblical character -- 3. Divine disciplinary devices : or the book of Jonah as a tractate on producing docile disciple-bodies -- 4. Cataloguing the monstrous : Jonah and the cani cacharis (or a concluding scientific postscript) -- 5. Taking stock : survivals, hauntings, Jonah and (Stanley) fish, and the Christian colonisation of the book of Jonah -- -- 2. Backwaters and underbellies -- 1. Jewish interpretation -- 2. Popular interpretation -- 3. On the strained relations between the backwaters and the mainstream : or how Jewish and popular readings are prone to bring on a bout of scholarly dyspepsia -- 4. Of survival, memes and life-after-death : on Jonah's infinite regurgitation and endless survival -- 5. Jonah on the oncology ward and the beached-up whale carcass, or the strange secular afterlives of biblical texts -- -- 3. Regurgitating Jonah -- 1. Of 'hot chestnuts', 'fluid puddings' and 'plots that do not shelter us' : some ruminations on the salvific properties of the Bible and literature -- 2. Regurgitating Jonah -- 3. In conclusion ... salvaging Jonah : the book of Jonah as the quintessential story and the most typical of biblical texts -- -- Bibliography -- Index.
Includes bibliographical references (pages 293-314) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc. -- History